Open Pit Mine Planning and Design, Two Volume Set & CD-ROM Pack, Third Edition. - Hustrulid, William A. (CRC Press, 2013)
Appropriate for diverse audiences, this book is an outstanding technical reference that provides the reader with an understanding of the fundamental principles associated with the design and planning of modern surface open-pit mines. The book is well-written and addresses topical subjects in a manner highly conducive for use in undergraduate and graduate education, as well as by a wide range of professionals interested in the subject. The text emphasizes the influence of economic and environmental considerations in mine design and planning, where applied engineering principles and approaches a.